Plurality, Power, and Mission Intercontextual Theological Explorations on the Role of Religion in the New Millennium - Philip L. Wickeri; Janice K. Wickeri; Damayanthi M. A. Niles ([London] : [Council for World Mission], 2000., 2010)
Papers presented at a meeting of the Network of Theological Enquiry (NOTE) in Cambridge, England, March 27-31, 2000. Hosted by the Christianity in Asia Project of the University of Cambridge. --Cf. p. 1.
Keywords: Missions -- Congresses. Missions -- Biblical teaching -- Congresses